Prospective study to evaluate the incidence of UTI in febrile infants and children < 5 years without focus of infection - Nagamani M. Kulkarni; Sadashiva B. Ukkali; A.N. Thobbi; Mohammed Zeeshan Desai; Khodaija Mahvish; Emad Rajgoli (Al Ameen Medical College, 2017)
Introduction: Among febrile infants and young children with UTIs, 75% have pyelonephritis, with consequences that, if missed, include renal scarring in 27-64% of patients, a 23% risk of hypertension, a 10% risk of renal failure, and a 13% risk of preeclampsia as adults. Approximately 13-15% of end-stage renal disease is believed to be related to undertreated childhood UTIs. As a result it is crucial to have high index of suspicion of UTI in febrile child without focus, also to have clear knowledge about pathogenesis, risk factors, indications for diagnostic tests and appropriate uses of antimicrobial agents in management of children with UTI. Materials & Methods: A hospital based observational prospective study was done at the Department of Paediatrics, Al Ameen Medical College & Hospital, during May 2015 to May 2016 and about 100 children were randomly selected between age group one month to 5 years who attended OPD or admitted with history of fever without obvious focus of infection. Results: A total of 100 cases of febrile children without any focus of infection between 1month - 5 years were studied. Out of them there were 56 boys and 44 girls with mean age being 22.5 months and 23.1 month respectively. Male to female ratio in study population is 1.12:1. Conclusion: 17 cases out of 100 were diagnosed to have UTI (urine culture positive cases) fulfilling the inclusion criteria there by showing incidence rate of 17%.